Dampak Pembangunan Bendungan di Tiongkok terhadap Keamanan Pangan Negara-Negara Hilir Sungai Mekong - Ridwan, Achmad Dhani; Idris, Nur Isdah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Mekong River is at the heart of the survival of the people of six countries that live around the upper and lower reaches of the Mekong River including Myanmar, Laos, Vietnam, Thailand, China, and Cambodia. The Mekong River is utilized to meet the national food security of six countries. One of the countries that utilize the Mekong River is China by building dams to meet the flow of environmentally friendly electricity for the Chinese people by utilizing dams for hydroelectric power plants built in the upper reaches of the Mekong River. This research uses the theory of neoliberalism and food security by using descriptive qualitative methodology to explain the impact of China's dam construction on the food security of countries downstream of the Mekong River. The impact of China's dam construction has an impact on the food security of countries downstream of the Mekong River because the majority of them utilize the Mekong River to meet their food needs and have professions as farmers and fishermen. The impact of the dam construction has an impact on changes in water quality that pollute the irrigation of rice fields of countries downstream of the Mekong River. In addition, many fish that live in the Mekong River immigrate to places with good water quality. Although China is a member of the Mekong River Commission, China has been unable to overcome the problems caused by the construction of dams at several points on the Mekong River.